2015
DOI: 10.1155/2015/736104
|View full text |Cite
|
Sign up to set email alerts
|

Role and Importance of IGF-1 in Traumatic Brain Injuries

Abstract: It is increasingly affirmed that most of the long-term consequences of TBI are due to molecular and cellular changes occurring during the acute phase of the injury and which may, afterwards, persist or progress. Understanding how to prevent secondary damage and improve outcome in trauma patients, has been always a target of scientific interest. Plans of studies focused their attention on the posttraumatic neuroendocrine dysfunction in order to achieve a correlation between hormone blood level and TBI outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 109 publications
(162 reference statements)
3
49
0
Order By: Relevance
“…Subsequent to an acute ischemic event, IGF‐1 crosses the disrupted blood–brain barrier and can induce differentiation of neural cells, including neurons, astrocytes, oligodendrocytes, and endothelial cells, in in vitro and animal models of traumatic brain injury and thus may exert its neuroprotective effects (Mangiola et al ., ). In parallel, insulin‐like growth factor binding protein‐3 (IGFBP‐3) modulates the bioavailability, transportation, and localization of insulin‐like growth factor‐I (IGF‐I), in animal stroke models especially when administered intranasally (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Subsequent to an acute ischemic event, IGF‐1 crosses the disrupted blood–brain barrier and can induce differentiation of neural cells, including neurons, astrocytes, oligodendrocytes, and endothelial cells, in in vitro and animal models of traumatic brain injury and thus may exert its neuroprotective effects (Mangiola et al ., ). In parallel, insulin‐like growth factor binding protein‐3 (IGFBP‐3) modulates the bioavailability, transportation, and localization of insulin‐like growth factor‐I (IGF‐I), in animal stroke models especially when administered intranasally (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…DNA methyltransferase 1 ( Dnmt1 ) is vital for neurological health and plasticity as it regulates tissue specific methylation patterns (Golshani et al ., ; Feng et al ., ). Furthermore, insulin growth factor‐1 (IGF1) plays a significant role in brain growth, development, and repair (Mangiola et al ., ), while perioxome proliferator‐activated receptor‐gamma coactivator 1‐α ( Pgc1‐α ) has been intimately linked to the regulation of energy metabolism and the stimulation of mitochondrial bioenergetics (Ji et al ., ). Finally, telomerase reverse transcriptase (Tert), maintains TL participating in cellular senescence and repair (Liu et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…The conventional consensus posited that leptin and IGF1 cross the blood-brain-barrier (BBB) and consequently elicit their effects by activating their respective receptors, Ob-Rb (leptin receptor isoform b) and IGF1R that are widely expressed in the brain. However, recent evidence has shown that both leptin [5-11] and IGF1 [10, 12, 13] are expressed endogenously in the brain and exert their effects in an autocrine / paracrine fashion. Leptin expression in the brain is critical as it serves as a neurotrophic cytokine that facilitates memory formation and enhances cognition by augmenting synaptogenesis [14].…”
Section: Introductionmentioning
confidence: 99%